In the Daylight of Our Existence (gta Verlag, 2025)
“Our survival requires that we alter our environment so that we can live and so that we can hold each other’s hands and so that we can kiss each other on the streets, and in the daylight of our existence, without terror and without violent and sometimes fatal reactions from the busybodies of America.”